Bosnia and Herzegovina : Accounting and Auditing - World Bank (Washington, DC, 2013)
This assessment of accounting and auditing (A&A) practices in Bosnia and Herzegovina is part of a joint initiative by the World Bank and International Monetary Fund (IMF) to prepare reports on the Observance of Standards and Codes (ROSC). The assessment focuses on the strengths and weaknesses of the accounting and auditing environment that influence the quality of corporate financial reporting, and includes a review of both statutory requirements and actual practice. It uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks and draws on international experience and best practices. This assessment updates the findings of the previous A&A ROSC conducted and published in Bosnia and Herzegovina in 2004. With a population of 3.8 million, Bosnia and Herzegovina is one of the smallest countries in Central and Eastern Europe. That population is largely made up of three constituent peoples: Bosniaks, Serbs, and Croats. Prior to the war, the three groups were more evenly distributed throughout the territory of Bosnia and Herzegovina, but now FBH's population is predominantly Bosniaks and Croats, while the RS has mostly Serbs. Since the war, Bosnia and Herzegovina has seen great progress in post-conflict reconstruction and development as well as in terms of reintegration and reconciliation. In recent years, Bosnia and Herzegovina has seen robust economic growth. After the war, this was initially driven by reconstruction efforts, but later private sector investment contributed to most of the growth. Between 2004 and 2008, the economy of Bosnia and Herzegovina grew at an average annual rate of 6 percent in real terms, and gross domestic product (GDP) growth peaked in 2007 at around 7 percent. Although economic activity started to weaken with the onset of the financial crisis, GDP growth was still relatively strong in 2008 at 5.4 percent. Both private investment and consumption saw strong growth, and export growth averaged 25 percent per annum over the period. Inflation was moderate during this period, amounting to just 3.8 percent in 2008 (year-on-year), despite a sharp rise in fuel and food prices in the first half of the year. The level of external public debt has been relatively low, but has been growing with the onset of the global crisis. In this context, this A&A ROSC aims to support the strategic objective of furthering the development of Bosnia and Herzegovina's corporate sector, improving access to finance for domestic enterprises, and reducing the cost of doing business in the country.